PERSEPSI WAJIB PAJAK TENTANG PAJAK RUMAH KOS DI KABUPATEN TULUNGAGUNG JAWA TIMUR - LINTANG PERMATA, RACHELLAURA (Jurnal Akuntansi AKUNESA, 2016)
ABSTRACT The purpose of this study was to determine the perception of taxpayers regarding tax boarding house in Tulungagung, East Java. Tulungagung currently growing and started many educational institutions, both formal and non-formal and shops are built so many peoplebuild a boarding house. Based regulations number 16 of 2010 explains the tax charged to businesses boarding houses, ie which has more than 10 rooms. In reality there are many owners don’t register, and didn’t pay taxes. This study used qualitative descriptive approach. Interviews with DISPENDA Tulungagung, BPPT and owners boarding houses both registered and unregistered.The results showed the perception of taxpayers regarding tax boarding houses from various sources to produce a wide range of opinions, some have suggested the tax boarding house is illegal levies, there are levied and some are‘nt. There’s also a claim that boarding house tax is to be applied for building Tulungagung to be more advanced. Keywords: perceptions tax payers, regulations number 16 of 2010, owners boarding house.